Major hepatectomy without blood transfusion： report of 51 cases - 芮静安 周立 刘馥迪 褚庆福 王少斌 陈曙光 曲强 魏学 韩凯 张宁 赵海涛 (Chinese medical journal, 2004)
Background Blood transfusion has been found to be a devastating factor for outcomes of hepatectomy. This study was to assess the value of major hepatectomy without blood transfusion.Methods We retrospectively studied 51 patients who had undergone major hepatectomy without blood transfusion, including 29 patients with primary liver cancer, from August 1997 to December 2000. Sixty patients undergoing major hepatectomy with blood transfusion including 48 patients with primary liver cancer served as controls. Hepatectomy was performed through normothermic interruption of the porta hepatis. Intraoperative ultrasonography was performed to define tumor margins, and an ultrasound dissector was used to dissect liver parenchyma.Results In the study group, the operative mortality and morbidity and 1-, 2-, and 3-year recurrence rates were 0%, 9. 8%, 24. 1%, 27.6% and 31.0%, respectively. In the control group, they were 3.3%, 28.3%, 43.5%, 54.3% and 58.7%, respectively. Significant differences were seen in morbidity and recurrence rates of patients with liver cancer between the two groups (P<0.05).Conclusion Major hepatectomy without blood transfusion can reduce postoperative morbidity and recurrence rate of patients with liver cancer.